Fracture and Permeability Properties of Artificial Fly Ash and Slag aggregate Concretes at Different Water-to-Cement Ratios (Journal of Material Science and Technology Research, 2020)
This study presents an experimental investigation on the effect of artificial aggregate utilization fracture and permeability properties of concretes. For this, two types of artificial aggregates, namely, artificial fly ash aggregate (AFA) from cold bonding agglomeration process of fly ash and Portland cement and artificial slag aggregate (ASA) from cold bonding agglomeration process of ground granulated blast furnace slag and Portland cement, were replaced with natural aggregate to coarse aggregate. Moreover, to investigate the influence of water-to-cement ratio, three different water-tocement ratios of 0.35, 0.45, and 0.55 were considered in the concrete production. The concretes were tested for the mechanical property in terms of as compressive strength, modulus of elasticity, and splitting, net flexural strength, and fracture energy and also permeability property such as water sorptivity, water penetration, gas permeability, and resistance to chloride ion penetration. The test results were also analyzed by means of statistical technique, namely, GLM-ANOVA. It was found that the use of cold bonded fly ash and slag aggregates were very effective on the performance characteristics of concretes depending on w/c ratio.